Clay footed giants - McGuire, Mark; Chevarier, Alain (Mad Cave Studios, LLC., 2024)
"Set in Montréal, Clay Footed Giants is a tragicomic meditation on parenthood, masculinity, and violence. Being a parent is so much harder than Pat ever imagined. While his partner Ester is away on a work trip, Pat loses his temper and transforms into a grizzly bear of a father, scaring his children and compounding his guilt. His friend Mathieu's stay-at-home-dad parenting advice is of no help, and only emphasizes Mathieu's professional shortcomings. The two men soon realize their children are mirrors reflecting old wounds that might never heal. Meanwhile, an unexpected package arrives from Pat's estranged father containing letters, photos and a mysterious medal from his time as a soldier in Vietnam, and it propels Pat's obsessive quest to understand his family's dark past. As Pat plunges deeper into his research, he and his family reach their breaking point. With help from Mathieu and Pat's mom, Pat digs down to the roots of their family's intergenerational trauma and learns how to heal himself in the process. Growth is possible, but so is oblivion. Eventually, the light pours in"--